Accelerated trypsin autolysis by affinity polymer templates. Issue 48 (4th August 2020) - Smolin, Daniel; Tötsch, Niklas; Grad, Jean-Noël; Linders, Jürgen; Kaschani, Farnusch; Kaiser, Markus; Kirsch, Michael; Hoffmann, Daniel; Schrader, Thomas
Abstract : Affinity copolymers specifically recognize the trypsin surface and act as templates for multiple protease molecules, leading to drastically accelerated autolysis – an unusual way for highly efficient enzyme inhibition at physiological conditions. Abstract : Self-cleavage of proteins is an important natural process that is difficult to control externally. Recently a new mechanism for the accelerated autolysis of trypsin was discovered involving polyanionic template polymers; however it relies on unspecific interactions and is inactive at elevated salt loads. We have now developed affinity copolymers that bind to the surface of proteases by specific recognition of selected amino acid residues. These are highly efficient trypsin inhibitors with low nanomolar IC50 levels and operate at physiological conditions. In this manuscript we show how these affinity copolymers employ the new mechanism of polymer-assisted self-digest (PAS) and act as a template for multiple protease molecules. Their elevated local concentration leads to accelerated autolysis on the accessible surface area and shields complexed areas. The resulting extremely efficient trypsin inhibition was studied by SDS-PAGE, gel filtration, CD, CZE and ESI-MS. We also present a simple theoretical model that simulates most experimental findings and confirms them as a result of multivalency and efficient reversible templating. For the first time, mass spectrometric kinetic analysis of the released peptide fragments gives deeper insight into the underlying mechanism and reveals that polymer-bound trypsin cleaves much more rapidly with low specificity at predominantly uncomplexed surface areas.